Ultrasonic parameters of the knee joint structure in adolescence - Shevchenko, Natalya (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
In order to determine age-specific peculiarities in the structure of knee joints their ultrasonic examination was carried out in children of both sexes at the age of 10-18 years. Results of studies of 100 clinically healthy adolescents without any signs of lesion of their articular apparatus are given. Changes in the articular cartilage were revealed: the latter was found out to gradually reduce its size in females and males during stages of their growth. Age- and sex-specific parameters of the joint space and suprapatellar bursa were revealed. The obtained results will make it possible to differentiate age-specific peculiarities in the structure of knee joints and their pathological changes in adolescents.